1999
DOI: 10.1038/sj.ijir.3900465
|View full text |Cite
|
Sign up to set email alerts
|

SSI Prize Essay for Male Erectile Dysfunction—Research ‘Sildenafil causes a dose- and time-dependent downregulation of phosphodiesterase type 6 expression in the rat retina‘

Abstract: Objectives: Some authors have advocated the daily use of sildena®l for prophylaxis against, or treatment of, erectile dysfunction. However, no information has been published to support such a dosage regimen. The safety pro®le of uninterrupted use of sildena®l has not been evaluated as it pertains to alteration of PDE type 6 in the retina. In the present study we investigated whether short-or long-term exposure to a variety of sildena®l doses affect the expression of an enzyme important in the normal phototrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 9 publications
1
16
0
1
Order By: Relevance
“…PDE6 is intensely localized at the rod and cone cells and has an important role in the phototransduction cascade. [17][18][19][20] PDE5 inhibitors show a PDE5 affinity only 10 times greater than PDE6, so some recent studies hypothesized that visual side effects of these drugs may be related to their cross-reactivity with PDE6.…”
Section: Discussionmentioning
confidence: 99%
“…PDE6 is intensely localized at the rod and cone cells and has an important role in the phototransduction cascade. [17][18][19][20] PDE5 inhibitors show a PDE5 affinity only 10 times greater than PDE6, so some recent studies hypothesized that visual side effects of these drugs may be related to their cross-reactivity with PDE6.…”
Section: Discussionmentioning
confidence: 99%
“…Acosta et al (2010) showed accelerated photoreceptor death in a rat model of RP (P23H rat) after a single dose of sildenafil. Sildenafil also decreased PDE6 expression in normal rats after long-term administration (Gonzalez et al, 1999). Thus, in retinal tissue where photoreceptors are under metabolic stress, sildenafil usage may push photoreceptors beyond the threshold of normal function and trigger dysfunction.…”
Section: Introductionmentioning
confidence: 90%
“…These abnormalities, which are usually mild and transient, include color tinge to vision, predominantly, and increased sensitivity to light or blurred vision. It is believed to be secondary to transient inhibition of phosphodiesterase type 6 (PDE6) when higher doses are used [4][5][6]. This cross-reactivity with PDE6 explains why these abnormalities are associated mainly with sildenafil and to a lesser extent with vardenafil, but not with tadalafil.…”
Section: Introductionmentioning
confidence: 95%